UNIVERSALITAS KESELAMATAN DI SION-IBU Sebuah Tafsiran atas Mzm 87 - Sinaga, Norbeth (LOGOS - Jurnal Filsafat Teologi, 2013)
Lord has chosen dan determined Zion-Jerusalem as his city. The election and the determination of Zion as a city of God was realized by building of the temple of God on it. Consecutively, Zion has a peculiarty in comparison with the other cities which arounding it. The peculiarity of Zion as a city of God be found at its determination as a place for doing a worship in the faith of God. Whoever believe in God and calling His Holy Name in Zion will be a new born in Zion as a mother, and a participant in program of salvation made of God. Either Israel or another nations who believe in God will rejoice enjoying a salvation in Zion-Mother.